Estimating Global Poverty; Towards a Unified Approach - Karshenas, Massoud (Journal of Income Distribution®, 2010)
In this article we discuss the compatibility of different global poverty estimates under a unified framework. We examine the updating of the rules of the international poverty lines under different Purchasing Power Parity exchange rate estimates and discuss the way this process has affected the latest World Bank poverty-line updates. The issue of the lack of comparability of the data of survey means and national accounts is also discussed, and it is argued that positions based on using one set of data as the indicator of average well-being, to the exclusion of the other, are problematic. We put forward an alternative approach, to deal with the inconsistency between the two data sources, which consists of calibrating the survey means, using the national-accounts data as external calibrating information. We show that combining the information in both sets of data in this way produces poverty measures which are more in congruence with other indicators of national poverty.